MAKNA PENDIDIKAN PADA MASYARAKAT SUKU AKIT DI DESA BANTAN TIMUR KECAMATAN BANTAN KABUPATEN BENGKALIS PROVINSI RIAU - ", Mistika; Asriwandari, Hesti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Akit community of the tribe in the village of Bantan Timur, majority of elementary education, because the background of primitive Akit tribe to education coupled with the socio economic conditions of Akit tribal people who livelihood as fisherman Gumbang. So the people of Akit tribe are not too concerned with their children’s education. The formulation of the problem in this study looked at the socio-ekonomic conditions in the community of Akit and knowing how the meaning of education in the comunity akit village Bantan Timur. Researchers by use seven subjects, six informans and one key informant are taken purposively (purposive sampling) with criteria that have been determined by the researcher. This researcher usus the theory of social action according to Max Weber. Where akit society is currently meaning education of their children, Akit tribe families meaning their children’s education higher so that life is better than now. Howebert, there are still families who interpret assume that if children are not interested in school and continue to be forced in the and will be in vain, so drop out of school then prefer to work. The results of this study show that of community members Akit Bantan Timur village is still relatively low viewed from social conditions the not willing to accept new things from the outside including formal education. House and income conditions are around five hundred thousand to one million permonth. The educational significance of the tribe community has been a shift from irrational acts to rationality, from no school to school.Keywords: Educational Meaning, Akit Tribe, Bantan timur Village